Laser Scanning of Trsat Castle as Part of Preservation Strategy of Rijeka Cultural Heritage (Proceedings of Faculty of Civil Engineering, 2019)
Trsat castle is one of the most famous heritage elements in Primorsko-goranska County. In 2015, as part of the renewal design, the City of Rijeka has commissioned the survey of the complex (almost 8000m²). The survey was done using the laboratory equipment of University of Rijeka. The aim of the paper is to illustrate the survey process, to analyze the possibility of combining laser scanning with other contemporary methods (drone survey, photo-modelling...), as well as to compare the results of the survey with the previous surveys of the complex, and to determine new data about the complex and discuss the results, especially the importance of such a complex survey for cultural heritage preservation.
Keywords: Gradina Trsat; Trsat Castle; laser scanning; survey of extantć